Ahuriri: "the dwelling place of the eel" and "a hopeless spot for a town": Napier in the 1850s - Marriage, Guy (Architectural History Aotearoa, 2012)
This paper looks at the early Pākehā settlers of Napier in the 1850s, and attempts to unravel what houses they had, where they were, and what styles they were built in. In the course of this investigation, an inevitable intersection with the pre-existing Māori iwi was unearthed and is also examined. It searches for the earliest existing housing remains in Hawkes Bay. So far, very little has been discovered remaining from the 1850s.